The Asthma Quiz for Kidz: A Validated Tool to Appreciate the Level of Asthma Control in Children - Francine M Ducharme; G Michael Davis; Francisco Noya; Harold Rich; Pierre Ernst (Canadian Respiratory Journal)
BACKGROUND: There is an urgent need to bridge the large gap between optimal and observed asthma control among Canadian children.